2020
DOI: 10.22541/au.159050476.60928563
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Therapeutic potential of ivermectin for COVID-19

Abstract: Background The aim of the present theoretical essay is to evaluate evidence published on the characteristics of the transcription of SARS-CoV-2 and explain the mechanism of action of ivermectin that may justify its therapeutic use in clinical practice for the treatment of COVID-19. Methods Laboratory studies, narratives, editorials and expert opinions on the subject were identified through a systematic search of the literature in the Medline/PubMed, Cochrane Library, Web of Science and Embase databases. Two bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Recent research has shown the strong antiviral properties of Ivermectin by inhibiting the replication of some RNA viruses in vitro . 33,34 Ivermectin is selectively concentrated in the pulmonary tissue, about 3 times more than the plasma concentration, and remains in the pulmonary tissue for a long time. 35 There is convincing evidence showing the therapeutic potential of Ivermectin for treating COVID-19.…”
Section: Ivermectin Shows Therapeutic Potential For Treating Covid-19...mentioning
confidence: 99%
See 2 more Smart Citations
“…Recent research has shown the strong antiviral properties of Ivermectin by inhibiting the replication of some RNA viruses in vitro . 33,34 Ivermectin is selectively concentrated in the pulmonary tissue, about 3 times more than the plasma concentration, and remains in the pulmonary tissue for a long time. 35 There is convincing evidence showing the therapeutic potential of Ivermectin for treating COVID-19.…”
Section: Ivermectin Shows Therapeutic Potential For Treating Covid-19...mentioning
confidence: 99%
“…103 Based on such evidence, it was suggested that Ivermectin has the potential to inhibit the SARS-CoV-2 replication and the cytokine-mediated pro-inflammatory response through blocking the formation of HIF-1α and IMP α/β1 complex. 34…”
Section: Ivermectin Inhibits Molecular Targets In Lung Cells Involved...mentioning
confidence: 99%
See 1 more Smart Citation
“…Reduction of viral loads in COVID-19 patients treated with some antiviral agents that can inhibit the binding of SARS-CoV-2 to host cells was found in various phases of clinical trials, indicating the inhibitory effect of these molecules on viral envelope proteins and their host cell receptors/co-receptors [ 31 , 32 ]. These are including antiviral drugs (ivermectin), neutralizing monoclonal antibodies (bamlanivimab and etesevimab), recombinant human monoclonal antibodies (casirivimab, imdevimab, and sotrovimab), and convalescence plasma [ 33 ]. At the beginning of the pandemic, several studies reported data on the antiviral activity of ivermectin, hydroxychloroquine alone, or in combination with azithromycin against SARS-CoV-2 [ 34 , 35 , 36 ].…”
Section: Sars-cov-2 Pathobiology and Treatment Optionsmentioning
confidence: 99%
“…Thus far, data indicate ivermectin is useful at the early stages of the disease, even the epidemiologic profile of COVID-19 shows significant differences regarding the age of patients for the affected countries and patients with comorbidity. 278 Therefore, large scale randomized clinical trials are necessary to standardize clinical, laboratory and image evaluations, as well as combined drug therapy with vitamins and zinc, for example. 279 Financially, ivermectin is inexpensive and its doses and protocols are well established for different purposes.…”
Section: Drug Repurposing For Covid-19mentioning
confidence: 99%